COMPARISON OF RELAXATION AND DISTRACTION TECHNIQUES IN REDUCING ANXIETY IN CIRCUMCISION PATIENTS - Agus Sulistyowati; Annisa, Faida (Universitas Nahdlatul Ulama Surabaya, 2022)
Background: Relaxation and distraction are nonpharmacologic techniques in the therapy of anxiety. In circumcision patients, the experience of anxiety is felt by the patients, either children or adolescent. Objective: The study aimed to compare between relaxation and distraction technique in reducing anxiety in circumcision patients. Methods: The study design was a pre-experimental two-group pretest-posttest research design. Total 36 respondents on this study that divided equal to two group (relaxation group and distraction group). The respondents have been assessed their anxiety level before and after the intervention (pre-test and post-test for each group). The instrument of anxiety was Hamilton Rating Scale for Anxiety (HARS). The statistics test used Wilcoxon Signed-Rank Test. Results: The Wilcoxon Signed rank test results for relaxation group was in a Z statistic of -3.317 which results in an exact p value of .001; and the results for distraction group was in a Z statistic of -2.449 which results in an exact p value of .014. Conclusion: There was different result between relaxation and distraction group that showed relaxation group reducing anxiety in higher score of a Z statistic compared with distraction group. However, those technique were effectively in decreasing the anxiety level of circumcision patients.